Natural infection with two genotypes of Cryptosporidium in red squirrels (Sciurus vulgaris) in Italy - Kváč, Martin; Hofmannová, Lada; Bertolino, Sandro; Wauters, Luc; Tosi, Guido; Modrý, David (Folia parasitologica, 2008)
We investigated the genotypes of Cryptosporidium infecting red squirrels (Sciurus vulgaris L.) in two areas of the Western Alps in Italy. Examination of 141 faecal samples from 70 red squirrels revealed oocysts of Cryptosporidium in 17 animals (24.3%). Based on 18S rRNA gene sequencing, two genotypes of Cryptosporidium species were found: 15 squirrels were positive for the Cryptosporidium ferret genotype and 2 for the Cryptosporidium chipmunk genotype I. The occurrence and intensity of Cryptosporidium infection did not differ between the study areas or sex. More than 85% of the positive animals were adults; however no difference was found between Cryptosporidium infection in the juvenile and adult age groups. Oocysts of the Cryptosporidium ferret genotype measured 5.5 ± 0.3 × 5.2 ± 0.2 µm (shape index 1.06) and the Cryptosporidium chipmunk genotype I 5.8 ± 0.3 × 5.4 ± 0.3 µm (shape index 1.07). Neonatal and adult CD1 and BABL/c mice inoculated with 1 × 103 fresh oocysts of both genotypes did not produce detectable infection.
Keywords: Animals; RNA, Ribosomal, 18S; ribozomální DNA; Genotype; nemoci hlodavců; feces; Feces; DNA, Ribosomal; Geography; Age Factors; Rodent Diseases; věkové faktory; Cryptosporidiosis; Molecular Sequence Data; Italy; Mice; genotyp; Itálie; Sciuridae; Mice, Inbred BALB C; zeměpis; myši; Sex Factors; molekulární sekvence - údaje; DNA, Protozoan; sexuální faktory; protozoální DNA; myši inbrední BALB C; RNA ribozomální 18S; Sequence Analysis, DNA; kryptosporidióza; zvířata; sekvenční analýza DNA; Cryptosporidium